INVESTIGATION OF WATER QUALITY PARAMETERS AT CHEYYERU RIVER WATER, ANNAMAYYA PROJECT, ANNAMAYYA DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The Annamayya Project (Cheyyeru) is a completed Medium Irrigation Project constructed across Cheyyeru, a tributary to the Penna River, situated near Badanagadda (V), Rajampet Mandal, Annamayya District. It's worth noting that water pollution poses significant challenges to life on Earth. Over time, reliance on river water has shifted to groundwater due to contamination concerns, impacting everyone's dependence on groundwater for fulfilling their needs. The interaction between surface water and groundwater means that pollution in one can lead to contamination in the other, thus affecting the global water cycle. The quality of water is influenced by its source and the level of environmental protection in the area. Some groundwater sources exhibit high levels of total dissolved solids (salinity), fluorides, iron, and manganese. The current study focuses on testing water samples collected from the Annamayya Dam for drinking and construction purposes.